Acquisition strategy and implementation - Hubbard, Nancy, 1963- (Ichor Business Books, 1999)
"Half of all acquisitions fail yet acquirers keep making the same mistakes time and time again: poor planning, a lack of communication and mishandled implementation. This book explores the process of acquiring through an in-depth look at the various stages: pre-acquisition planning, communication during the deal and implementation."--BOOK JACKET. "The book also explores the history of acquisitions, their trends globally, and reasons for success and failure. The psychology of employee behaviour during acquisition is examined, as well as what acquirers can do to mitigate employee concerns and to motivate the work force during the acquisition process. Throughout the book, practical tools and applicable research are used to highlight the latest in acquisition best practice. In addition, five case studies are used to show how different companies approached their respective acquisitions with varying degrees of success."--BOOK JACKET.